HUBUNGAN KEPEMIMPINAN KETUA KELOMPOK TANI DENGAN EFEKTIVITAS KELOMPOK TANI DI KECAMATAN PUSOMAEN KABUPATEN MINAHASA TENGGARA (STUDI KASUS: KELOMPOK TANI TEKAD BERSAMA DESA MINANGA SATU) - Kangki, Neyky Rayfi; Pakasi, Caroline Betsi Diana; Benu, Noortje Marsellanie (AGRI-SOSIOEKONOMI, 2022)
This research aims to examine and analyze the relationship between the leadership of the farmer group leader and the effectiveness of the “Tekad Bersama” farmer group in Minanga Satu Village, Pusomaen District, Southeast Minahasa Regency. This research was conducted for 3 months starting from September to November 2021. The data used in this study were primary data and secondary data. Primary data was obtained from interviews with members of farmer groups using a list of questions that had been developed directly using a questionnaire. Secondary data were obtained from the Minanga Satu village office, as well as literature studies from the results of previous studies related to research and articles from print media and the internet. The method used in sampling is done by census, where all members of the population are used as samples with the number of members of the farmer group is 15 people. While the analytical method used is the Spearman Rank Coefficient Correlation Test (rs). The results showed that the leadership of the collective determination farmer group in Minanga Satu village was in the high category. The effectiveness of the Tekad Bersama farmer group in Minanga Satu Village is in the high category. From the results of the Spearman Rank test and the significance test at the 95% confidence level, it was found that the relationship between the leadership of the head of the farmer group and the effectiveness of the farmer group had a significant relationship.